Height predict incident non-alcoholic fatty liver disease among general adult population in Tianjin, China, independent of body mass index, waist circumference, waist-to-height ratio, and metabolic syndrome - Shubham Kumari; Xuena Wang; Yunyun Liu; Yeqing Gu; Yuhan Huang; Qing Zhang; Li Liu; Ge Meng; Hongmei Wu; Shaomei Sun; Xing Wang; Ming Zhou; et al. (BMC, 2020)
Abstract Background Early-life hormonal and nutritional factors can greatly influence the risk of non-alcoholic fatty liver disease (NAFLD). Adult height is a simple marker for these factors. This study aimed to investigate the association between adult height and NAFLD. Methods We performed a prospective cohort study of 35,994 participants aged 25 years or over with measured height at baseline. NAFLD was diagnosed by abdominal ultrasound and self-reported history of alcohol intake. Multivariable Cox proportional hazards regression models were conducted to assess the gender-specific association between height and the risk of NAFLD. Results During a follow-up period of 5.5 years, 6245 of 35,994 subjects developed NAFLD. The adjusted hazard ratios (95% confidence interval) of NAFLD for increasing quintiles of height were 1.00 (reference), 0.82 (0.73, 0.92), 0.84 (0.73, 0.97), 0.72 (0.61, 0.85) and 0.63 (0.50, 0.79) (P for trend < 0.0001) in males, and 1.00 (reference), 1.00 (reference), 0.80 (0.69, 0.91), 0.72 (0.61, 0.85), 0.60 (0.49, 0.74) and 0.45 (0.35, 0.59) (P for trend < 0.0001) in females, respectively. Conclusions A higher adult height was associated with lower risk of NAFLD among males and females in Tianjin, China.